A compact bandpass filter using microstrip hairpin resonator for WLAN applications - Azam, S. M. Kayser; Ibrahimy, Muhammad Ibn; Motakabber, S. M. A.; Hossain, A. K. M. Zakir (IEEE Explore, 2018)
This work represents a microstrip hairpin resonator-based bandpass filter for Wireless Local Area Network (WLAN). Two short-circuited microstrip comb-lines have been coupled at the two sides of a rectangular-loop to construct the hairpin resonator. The Taconic TLX-8 material has been used as the substrate to design the filter at a center frequency of 2.45 GHz. The designed filter exhibits a two-pole Chebyshev response with an insertion loss of -0.37 dB and a minimum return loss of -34.03 dB. This compact filter has a fractional bandwidth of 4.37% which sharply selects the entire bandwidth of WLAN frequencies.